Penyelesaian Kredit Macet di Koperasi Sumber Kasih Desa Tangeb, Kecamatan Mengwi, Kabupaten Badung - I Kadek Nova Astrawan; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
Indonesia is a developing country with various kinds of economic development. Bound by government regulations, the community cannot act arbitrarily and must follow applicable norms. The government in an effort to equalize the welfare of its people creates a forum for community associations to manage their funds or borrow funds to open a business. The purpose of this study is to reveal the legal arrangements for bad loans at KSU Sumber Kasih, Tangeb village and the settlement of bad loans at KSU Sumber Kasih, Tangeb village. This research applies normative research methods. Sources of data used in the form of primary and secondary legal materials. This research was conducted by looking for direct data from the field and through legal science books and connecting with the issues raised and then linking them to the current legislation which was then analyzed systematically. The results of the study reveal that Rural Banks are the government's solution to provide convenience to the community but with terms and conditions in the lending process. Every community who wants to borrow money for certain purposes can be done at BPR, those who want to borrow capital must have collateral which will later be calculated according to the desired loan, but it is not uncommon for bank staff not to think about the amount of collateral used with borrowed funds, this often happens. default